Feminism against Beauty Standards in South Korea: Force Creates Resistance - Hamdon, Syamimi Waznah; Bintang Timur, Fitriani (Journal of Techno-Social, 2021)
This article explores about the resistance that women in South Korean made in regards to the unrealistic beauty standards that is projected for the Korean women in order for the to get a place in social involvement. Women in South Korea are marginalized, and although the population in women in South Korea is 49.93% in 2019 which is a balance number for both female and male, but their voices remain as minority within the society involvement. In regards, they are often isolated from important social and professional networks and subjected to the negative stereotyping of becoming a feminist. Women in Korea are ought to have the attributes of beauty standards or else, society would judge them and this is a sign that women are trapped with this kind of projection thus it become a barrier for them to grow themselves. Why beauty standards matter among women in South Korea and how global feminism influence women in South Korea to create a resistance against rigid beauty standards in South Korea? To explore this question, this study used qualitative method with phenomenology approach. Drawing on the concept of transnational feminism as well as feminist standpoint theory, this study expected to find the actions taken by the women in South Korea to oppress the idea of objectifying women into certain characteristic of beauty and the oppression of â€œpretty priviledgeâ€. Keywords: Feminism, transnational feminist, beauty standards, objectifying.